Rethinking and Renewing Educational Paradigms, Theories, and Pedagogies in Entrepreneurship Education - Fayolle, Alain; Loi, Michela; Suomi, Kati; Heljakka, Katriina; Linan, Francisco (Sage, 2026)
Studies highlight that Entrepreneurship Education (EE) is now a well-established research field, yet fundamental issues concerning its theoretical foundations and societal role remain highly debated. To substantiate this debate and strengthen theoretical and epistemological perspectives, the call for this special issue identified three complementary macro topics deserving of research attention: philosophical and theoretical issues, pedagogies and educational models, and critical perspectives. This introduction offers a comprehensive review of the EE literature that explicitly addresses philosophical concerns or introduces well-defined perspectives, identifying four partially overlapping temporal phases that reflect shifting analytical foci on EE conceptualization and philosophical engagement. The analysis shows that while pedagogical models and educational practices have been extensively explored, deeper philosophical inquiry and critical reflection on issues of inclusion, gender, and social responsibility have emerged more explicitly only in recent years. The papers included in our special issue, accordingly, tend to address important gaps underlined in both our call and literature review.